2000
DOI: 10.1023/a:1006765300028
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study examined the impact of providing and receiving support on the quality of life (QOL) of the elderly. Trained interviewers conducted face-to-face interviews with 714 rural community residents aged 60 and over in Korea. Subjects were asked a series of structured questions including age, sex, living arrangement, physical functions, and the frequency of providing and receiving support in their network (spouse, children, and friends). The Philadelphia Geriatric Center Morale Scale was used to measure degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(22 citation statements)
references
References 19 publications
4
16
1
1
Order By: Relevance
“…These researchers found that "providing informal support to others appears to exert a positive effect on well-being in later life" (p. P308). Similar results were presented in a study on social support, exchange, and quality of life among elderly Koreans (Kim et al 2000). Apparently, providing support to adult children can enhance the self-esteem of older adults and contribute to feelings of independence, which in turn can affect life satisfaction.…”
Section: Discussionsupporting
confidence: 81%
“…These researchers found that "providing informal support to others appears to exert a positive effect on well-being in later life" (p. P308). Similar results were presented in a study on social support, exchange, and quality of life among elderly Koreans (Kim et al 2000). Apparently, providing support to adult children can enhance the self-esteem of older adults and contribute to feelings of independence, which in turn can affect life satisfaction.…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, tangible support includes material aid and behavioral assistance. Some studies combined 3 subcategories other than tangible support into emotional support and simplified social support with 2 aspects 28,29…”
Section: Discussionmentioning
confidence: 99%
“…Aunque se han encontrado correlaciones positivas entre dar y recibir ayuda (Grundy, 2005;van Tilburg, & Broese van Groenou, 2002), también existen trabajos que no apoyan ninguna de las dos teorías (Kim, Hisata, Kai, & Lee, 2000). Dado que las evidencias sobre la validez de estas teorías suelen centrarse de manera general en las relaciones familiares y sociales, en este trabajo se ponen a prueba sus postulados, considerando el intercambio de apoyo entre miembros específicos de la red social del individuo.…”
unclassified